Peran Mediasi Motivasi Kerja Pada Pengaruh Kecerdasan Emosional Dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior Pegawai Pemerintah - Biswan, Ali Tafriji (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2019)
The study was to determine the effect of emotional intelligence, organization commitment, and work motivation to organizational citizenship behavior of government employees at T ax T raining C enter. This research tried to explore and determine problems concerning with employees organizational citizenship behavior . The research was conducted in Tax Training Center with a population 63 and samples taken 54 by using quantitative approach with path analysis methods. The research of hypothesis testing show that there are: (1) positive direct effect of emotional intelligence on organizational citizenship behavior ; (2) positive direct effect of organization commitment on organizational citizenship behavior ; (3) positive direct effect of motivation on organizational citizenship behavior ; (4) positive direct effect of emotional intelligence on motivation: (5) positive direct effect of organization commitment on motivation ; and (6) positive direct effect of emotional intelligence on organization commitment. Therefore to improve organizational citizenship behavior of government employees at Tax Training Center, organization need to increase their emotional intelligence, organization commitment, and work motivation.